ALKANES (Proceedings of International Educators Conference, 2024)
In organic chemistry, an alkane, or paraffin, is an acyclic saturated hydrocarbon. In other words, an alkane consists of hydrogen and carbon atoms arranged in a tree structure in which all the carbon–carbon bonds are single. This article describes the Alkanes.